Small-molecule inhibitors of protein-protein interactions - Vassilev, Lyubomir; aFry, David; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
abody> In this volume, the editors have collected the knowledgeable insights of a number of leaders in this field - researchers who have achieved success in addressing the difficult problem of inhibiting protein-protein interactions. These researchers describe their unique approaches, and share experiences, results, thoughts, and opinions. The content of the articles is rich, and in terms of scope ranges from generalized approaches to specific case studies. There are various focal points, including methodologies and the molecules themselves. Ultimately, there are numerous lessons to be taken away from this collection, and the editors hope that this snapshot of the current state of the art in developing protein-protein inhibitors not only pays tribute to the past successes, but also generates excitement about the future potential of this field.
Preface -- Hydrogen-bonded synthetic mimics of protein secondary structure as disruptors of protein-protein interactions -- Small-molecule inhibitors of IL-2/IL-2R: lessons learned and applied -- Small Molecule Inhibitors of the Human Papillomavirus E1-E2 Interaction -- Design of small-molecule Smac mimetics as IAP antagonists -- Small-molecule inhibitors reveal a new function for Bcl-2 as a pro-angiogenic signaling molecule -- Small-molecule modulators of c-Myc/Max and Max/Max interactions.- Small-molecule inhibitors of the p53-MDM2 interaction -- Subject index.
Electronic reproduction.
Keywords: Protein-protein interactions; Enzyme inhibitors; Protein Binding -- drug effects; Small Molecule Libraries; Electronic books